Case Report: A Rare Presentation of NSAID-Induced Secondary Membranous Nephropathy in a Pediatric Patient - Shah, Siddharth; Elder, M. Asope; Hata, Jessica (Frontiers in Pediatrics, 2021)
Background: Membranous nephropathy (MN) is a common cause of nephrotic syndrome in adults, but it is responsible for less than 5% of nephrotic syndrome cases in children. MN has primary and secondary forms. Secondary MN is caused by viral infections, autoimmune diseases like lupus, or drugs. Nonsteroid anti-inflammatory drug (NSAID)-induced secondary MN is rarely described in the pediatric population. Thus, the clinical presentation and time to recovery are vastly unknown in the pediatric subgroup. Clinical Presentation: We report a case of a 15-year-old female who presented with acute onset of nephrotic range proteinuria, significant hypoalbuminemia, hyperlipidemia, and lower extremity edema related to the presence of the nephrotic syndrome. She had a history of ibuprofen use periodically for six months before the presentation because of menstrual cramps and intermittent lower abdominal pain. After the presentation, we performed a renal biopsy that reported stage 1–2 MN, likely secondary. The phospholipase A2 receptor (PLA2R) antibody on the blood test and PLA2R immune stain on the renal biopsy sample were negative. We performed a comprehensive evaluation of the viral and immune causes of secondary MN, which was non-revealing. She had stopped ibuprofen use subsequent to the initial presentation. She was prescribed ACE inhibitor therapy. After six months of ACE inhibitor treatment, the proteinuria had resolved. Conclusion: Proteinuria can last for several weeks when NSAID induces secondary MN and nephrotic syndrome. With the widespread use of NSAIDs prevalent in the pediatric community, further studies are needed to evaluate and study the role of NSAIDs in this condition.